2013
DOI: 10.4304/jltr.4.2.301-309
|View full text |Cite
|
Sign up to set email alerts
|

Blended Learning in a University EFL Writing Course: Description and Evaluation

Abstract: Abstract-Though blended learning had been continuously adopted in an Academic English Writing course (AEW) in a key university in Beijing, no attempts had been made to describe this new learning environment or investigate its effectiveness and impact. To fill in the gap, the present paper describes and evaluates blended learning in this AEW course in terms of course design, material development and presentation, assignment submission and grading, student involvement, teacher reflection, and student evaluation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 35 publications
2
52
0
5
Order By: Relevance
“…Collaborative writing tasks cultivate students' negotiation and social interaction skills in the classroom, decrease their WA when completing the writing tasks alone and promote students' self-confidence (Rollinson, 2005;Mulligan & Garofalo, 2011;Liu, 2013) In addition, sharing ideas via negotiation and collaboration helps students collect various points of view about the writing task and reduces the WA accompanied with difficulty of the writing task (Ansarimoghaddam & Bee, 2013). Moreover, Jafari and Ansar (2012) and Larsen (2012) reported that students who write collaboratively achieve more significant improvement in their writing skills and abilities than those who write alone.…”
Section: "It Exposed Us To Enjoyable Learning Activities In Writing Amentioning
confidence: 99%
See 3 more Smart Citations
“…Collaborative writing tasks cultivate students' negotiation and social interaction skills in the classroom, decrease their WA when completing the writing tasks alone and promote students' self-confidence (Rollinson, 2005;Mulligan & Garofalo, 2011;Liu, 2013) In addition, sharing ideas via negotiation and collaboration helps students collect various points of view about the writing task and reduces the WA accompanied with difficulty of the writing task (Ansarimoghaddam & Bee, 2013). Moreover, Jafari and Ansar (2012) and Larsen (2012) reported that students who write collaboratively achieve more significant improvement in their writing skills and abilities than those who write alone.…”
Section: "It Exposed Us To Enjoyable Learning Activities In Writing Amentioning
confidence: 99%
“…Secondly, the use of blended learning method had enhanced the EFL students' interaction and encouraged them to be highly motivated and become more autonomous and independent learners. Consequently, the high motivation and autonomy had led to better writing performance (Liu, 2013).…”
Section: The Effects Of Cblwe On Students' Wa and Wpmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study revealed that students who were taught using blended learning techniques scored good grades (Schwankl, 2013). Liu (2013) was successful in evaluating blended learning in terms of material development, grading, course design, student evaluation, and teacher reflection. The results showed that blended learning increased the student-student and student-teacher interactions.…”
Section: Teacher 4 Stated 'I Like To Use Search Engines But I Do Not mentioning
confidence: 99%